Design and evaluation of a modified underwater cycle ergometer - Chen, A. A.; Kenny, G. P.; Johnston, C. E.; Giesbrecht, G. G. (Canadian Journal of Applied Physiology, 1996)
An underwater cycle ergometer was designed consisting of an aluminum cycle frame in water connected with a 1:1 gear ratio to a mechanically braked standard cycle ergometer supported above the water. Three progressive maximal exercise tests were performed (n = 10): (a) the underwater ergometer in water (UEW), (b) underwater ergometer in air (UEA), and (c) a standard cycle ergometer in air (SEA). At submaximal power outputs, oxygen consumption (VO2) and heart rate (HR) were generally lower in the SEA condition (p < .05), indicating that exercise in the upright position was more efficient. Exercise in water (UEW) resulted in lower total exercise duration, maximal HR, and maximal Tes than in air conditions. The upright position (SEA) resulted in greater total exercise duration and maximal power output than the semirecumbent positions. Because of positional differences between the standard and underwater ergometers, air-water comparisons should be made by using the underwater ergometer in water and on land.